PENGARUH SPESIALISASI INDUSTRI AUDITOR, AUDIT FEE, DAN AUDIT TENURE TERHADAP TAX EVASION (Studi Empiris pada Perusahaan Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Maharani Darmawanti; Tarmizi Achmad (Diponegoro Journal of Accounting, 2026)
Tax evasion remains a critical issue in the taxation system as it directly reduces government revenue and undermines the credibility of corporate financial reporting. This study aims to empirically examine the effect of auditor industry specialization, audit fee, and audit tenure on tax evasion in energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This study employs secondary data and uses a purposive sampling method, resulting in 105 firm-year observations. The results indicate that auditor industry specialization has a negative and significant effect on tax evasion, suggesting that auditors with industry-specific expertise are more effective in monitoring and reducing tax evasion practices. Meanwhile, audit fee and audit tenure do not have a significant effect on tax evasion. These findings imply that higher audit fees and longer auditor–client relationships do not necessarily enhance auditors’ ability to detect tax evasion.